(untitled) (Bioresearch Communications, 2026)
Cyanobacteria is promising source of third generation biofules which led to the current interest of genetically modified strains. The isolation of fully segregated mutant cells is slow and tedious due to the presence of multiple chromosome copies Mutant isolation from liquid media can readily accelerate the selection process, although remain as mixed population with varying segregation status. This study was focused on two exploratory approaches of mutant screening from liquid culture via plate reader and FACS. As both the plate reader and FACS can detect cellular fluorescence intensity expressed by a fluorescent reporter protein, four novel fluorescent antibiotic resistance cassettes were constructed via N-terminal tandem fusion with eYFP. The bifunctionality of the fusion proteins was demonstrated by the minimal impact on the extent of antibiotic resistance conferred by the fusions and fluorescence was demonstrated for 3 of the 4 fusions generated. It required only 11 days to isolate eYFP +ve cells from a mixed population (starting at 0.001% eYFP). The optical setting available with the flow cytometer was not optimal to set a gating parameter to detect all the eYFP +ve cells, suggests the necessity of an alternative laser or to change the fluorescent protein. Additionally, two suicide vectors were constructed to incorporate the fusion cassette into cyanobacteria genome by replacing two native sites. The molecular tools and strategies developed in this study can also be applicable in the engineering of other polyploidy bacterial species and thus could benefit the wider scientific community. Bioresearch Commu. 12(1): 2010-2023, 2026 (January)